Sintomas de deficiências de macronutrientes em pepineiro - Carmona, Víctor Manuel Vergara [UNESP] (2015)
There exists a necessity for production systems to become more efficient with less impact on the environment. Among many factors of productivity, there is the adequacy of crop fertilization, which is related to the mineral nutrition of the plant and the recognition of nutritional deficiencies. In the present study, the initial symptoms and the alterations caused by nutritional deficiencies in the cucumber were described and photographed, and the concentrations of the macronutrients omitted from the leaves that exhibited the deficiencies were analyzed. The experimental design was completely randomized into six treatments with three replicates per treatment. The treatments were the complete nutrient solution and the individual omissions of N, P, K, Ca and Mg from the nutrient solution. The treatments were applied at the initiation of fructification. Physiological disorders of N, P, K, Ca and Mg in the cucumbers were observed at 3, 20, 2, 3 and 5 days respectively, after the omission of the nutritive solution. N and P deficiencies were characterized by chlorosis and browning, respectively. The lack of K was shown as chlorosis in the margins of the leaf lamina, progressing to tissue necrosis. The deficiency of Mg was characterized by internerval chlorosis that also progressed to tissue necrosis. The symptoms of N, P, K, and Mg deficiencies began on the intermediate leaves. The symptoms of Ca deficiency were observed in the leaves next to the apical meristems, showing contortions of the leaves and necrosis on the marginal tissues of the leaf blade. When the symptoms of deficiency were visualized, the concentrations of N, P, K, Ca and Mg in the leaves with the disorder were 18.9; 1.5; 9.5; 1.5 and 1.2 g kg-1, respectively